2014
DOI: 10.1371/journal.pone.0094635
|View full text |Cite
|
Sign up to set email alerts
|

ZFP580, a Novel Zinc-Finger Transcription Factor, Is Involved in Cardioprotection of Intermittent High-Altitude Hypoxia against Myocardial Ischemia-Reperfusion Injury

Abstract: BackgroundZFP580 is a novel C2H2 type zinc-finger transcription factor recently identified by our laboratory. We previously showed that ZFP580 may be involved in cell survival and growth. The aim of this study was to elucidate whether ZFP580 is involved in the cardioprotective effects of intermittent high-altitude (IHA) hypoxia against myocardial ischemia-reperfusion (I/R) injury.Methods and ResultsAfter rats were subjected to myocardial ischemia for 30 min followed by reperfusion, ZFP580 expression in the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, it was also reported that ATRA activated SM22a expression through KLF4 binding to its ciselements in an acetylation-dependent manner and inhibited VSMC differentiation [14]. Our previous studies have shown that the novel zinc-finger transcription factor ZFP580 plays important roles in endothelial biology and cardiovascular disease [24][25][26]. We then evaluated the role of ZFP580 in VSMC biology using both gain-and loss-of-function analyses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it was also reported that ATRA activated SM22a expression through KLF4 binding to its ciselements in an acetylation-dependent manner and inhibited VSMC differentiation [14]. Our previous studies have shown that the novel zinc-finger transcription factor ZFP580 plays important roles in endothelial biology and cardiovascular disease [24][25][26]. We then evaluated the role of ZFP580 in VSMC biology using both gain-and loss-of-function analyses.…”
Section: Discussionmentioning
confidence: 96%
“…Bioinformatic analyses revealed that ZFP580 is also a C2H2 (Cys2-His2) zinc-finger protein that contains 172 amino acids, and 97% of the amino acid sequence is consistent with ZNF580. Our previous study has shown that ZFP580 had an anti-apoptotic effect on myocardial ischemia reperfusion injury [24]. The expression of ZFP580 significantly changed in VSMCs with intimal neovascularization.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, the reduction of cell necrosis and apoptosis are thought to be effective Li/Xie/Lin/Huang/Liang/Huang/Jiang: Renalase in Myocardial Ischemia Reperfusion Injury expression in SD rats [20][21][22][23][24][25][26]. We set the Left anterior descending coronary artery LAD) blocking time at 45 min and the reperfusion time at 4 h based on our previous preliminary experiment [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that ZNF580 is ubiquitously expressed in human tissues, and serves important roles in maintaining normal cell functions, including migration and proliferation (4,5). ZFP580 is the murine homologue of ZNF580, research regarding cloned ZFP580 (6) revealed that intermittent hypoxia could induce expression, which displayed an anti-apoptotic role during early phase ischemia-reperfusion injury (7). However, the mechanism and signaling pathways underlying the anti-apoptotic effects of ZFP580 have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%